DKI Jakarta’s Regional Government Speech Act Analysis and Public Response to Air Pollution Issue on Instagram Platform - Gusthini, Misyi; Istiningdias, Dini Sri (Journal of Pragmatics and Discourse Research, 2024)
The problem of air pollution in Indonesia, especially in Jakarta, makes the society pay attention to this Indonesian’s capital city, and they give some opinion in social media such as Twitter, Instagram, Facebook, or other’s platform. The Jakarta’s government gave some responses through Instagrams platform, at @pandemictalks account about the Jakarta’s air pollution. This research is conducted to figure out how the use of linguistic feature, especially speech act used by the Jakarta’s government in facing the societies responses about the air pollution issue. Heru Budi as the PIC of Jakarta’s Governor, produced some illocutionary speech act such as representative, expressive, and directive illocutionary act. The researchers found not only the locution and illocutionary act, but also the perlocutionary act and its meaning that showed in the comment column of Instagram written by the public as the response of Heru’s utterances about air pollution problem. The researchers used descriptive qualitative method by Djajasudarma (2006) for data analyses and explained the data by describing through words. Data sources taken from the Instagram in @pandemictalks account, and the data are 7 slides of Jakarta’s government statement, also the response with the most like from the comment column. In analyzing the meaning of illocutionary act (Yule,1996), the researchers seeing from the contextual appear from the utterances. The data also showed that one utterance consists of two illocutionary acts meaning, such as representative + directive, and representative + expressive. The research findings are 4 data illocutionary act found in the object of study, and 3 perlocutionary act taken from the most love get from the public users of Instagram in that post, that represent about what the public opinion toward Heru’s statement about air pollution. Heru Budi uttered 2 data representative directive, 1 data representative expressive, and 1 data expressive act. In conclusion, the researchers also find most of society are disappointed by Budi’s statement, represent through 1 data representative directive act, 1 data expressive act, and 1 data representative expressive act.